The Canadian clinician-scientist training program must be reinstated - David D.W. Twa; Jordan W. Squair; Michael A. Skinnider; Jennifer X. Ji (The Journal of Clinical Investigation, 2015)
Clinical investigators within the Canadian and international communities were shocked when the Canadian Institutes of Health Research (CIHR) announced that their funding for the MD/PhD program would be terminated after the 2015–2016 academic year. The program has trained Canadian clinician-scientists for more than two decades. The cancellation of the program is at odds with the CIHR’s mandate, which stresses the translation of new knowledge into improved health for Canadians, as well as with a series of internal reports that have recommended expanding the program. Although substantial evidence supports the analogous Medical Scientist Training Program in the United States, no parallel analysis of the MD/PhD program has been performed in Canada. Here, we highlight the long-term consequences of the program’s cancellation in the context of increased emphasis on translational research. We argue that alternative funding sources cannot ensure continuous support for students in clinician-scientist training programs and that platform funding of the MD/PhD program is necessary to ensure leadership in translational research.